Effects of Self-Efficacy Beliefs and Managerial Attitudes on the Relationship between Budget Participation and Performance - Piccinin, Yvelise (2022)
Objective: To analyze the effects of self-efficacy beliefs and managerial attitudes in the relationship between budget participation and managerial performance of 225 professional controllers, managers and coordinators of controllership of companies in the southern region of the country. Method: A descriptive, survey and quantitative research was carried out with data analysis by structural equation modeling. The sample had the voluntary participation of 225 people from the companies that were the focus of the analysis. Results: It was evidenced that budget participation influences self-efficacy beliefs and commitment to budget goals. However, it had no influence on work engagement. The findings confirm the indirect cognitive (self-efficacy beliefs) and affective (work engagement and commitment to goals) effects on the relationship between budget participation and managerial performance. Contribution: From a practical point of view, it reveals the importance of developing self-efficacy beliefs, since these have been shown to be determinants of human behavior at work. It also provides empirical validation for theories little explored in management accounting (Social Cognitive Theory and Affective Event Theory) and contributes to the literature that examines cognitive and behavioral aspects in the relationship by seeking to understand under what conditions budget participation results in better managerial performance.